The Effect of Body Weight on Eating Behavior and Risk for Diabetes, Health Literacy among Turkish Adults: Effect of Body Weight on Eating Behavior - Ulas Kadioglu, Bircan; Soylar, Pınar (Progress in Nutrition, 2021)
Objective This study was aimed to investigate the effect of body weight on eating behavior, risk for diabetes and health literacy of individuals in a primary healthcare center.Design Body weight, eating behavior, risk for diabetes and health literacy level were evaluated in this cross-sectional descriptive study. A total of 210 individuals with normal weight (BMI of 18.5 to